Hydrogel for promoting cartilage repair by piezoelectric effect, preparation method and application thereof
By preparing a three-dimensional piezoelectric hydrogel of potassium sodium niobate, polyvinyl alcohol and polyacrylic acid, and utilizing the piezoelectric effect to respond to electrical stimulation, the problem of hyaline cartilage regeneration in the existing technology was solved, and biodegradable hyaline cartilage regeneration and motor function recovery were achieved.
Patent Information
- Application Number
- CN202311103901.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2043-08-30
AI Technical Summary
The existing technology lacks effective methods to regenerate hyaline cartilage. Existing hydrogel materials have insufficient mechanical properties and it is difficult to maintain the cartilage repair effect in the long term. In addition, piezoelectric polymers such as PVDF are not biodegradable, and PLLA and PLA have weak piezoelectric properties.
A biodegradable three-dimensional piezoelectric hydrogel was prepared using potassium sodium niobate (KNN), polyvinyl alcohol (PVA) and polyacrylic acid (PAA). The piezoelectric effect was used to respond to radio stimulation, promote the chondrogenic differentiation of stem cells and endogenous angiogenesis, and achieve the regeneration of hyaline cartilage.
By regulating the phase structure of KNN, increasing the polarization direction of the electric dipole inside the material, and utilizing the excellent properties of polyvinyl alcohol and polyacrylic acid, a biodegradable three-dimensional piezoelectric scaffold was prepared to promote the regeneration of hyaline cartilage in cartilage defects and restore motor function.
Smart Images

Figure CN116942922B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to a regenerated hydrogel, in particular a hydrogel for promoting cartilage repair by using a piezoelectric effect, a preparation method and application thereof, and belongs to the technical field of biomaterials. BACKGROUND
[0002] Joint cartilage injury is a common and frequently-occurring disease, which seriously affects the daily activities and quality of life of patients. Cartilage injury diseases include not only degenerative disease osteoarthritis but also focal joint cartilage defects caused by sports injuries. Osteoarthritis mainly affects the general middle-aged and old people, and is one of the most common diseases of the middle-aged and old people, which leads to serious chronic pain and joint dysfunction, and brings great pain and mental burden to the middle-aged and old people. Therefore, reasonably and effectively repairing cartilage injury can not only solve the pain of the general patients, but also greatly reduce the social and economic burden. Joint cartilage is a layer of hyaline cartilage covering the bone end, has no blood vessel distribution and no self-repairing ability. At present, there is no active and effective treatment for cartilage injury, and only the progress of the disease can be delayed, and finally joint replacement surgery is performed. Therefore, it is of great significance to regenerate hyaline cartilage, repair cartilage injury, prevent further cartilage degeneration and avoid joint replacement surgery for patients. Regenerating natural cartilage and restoring the original smooth joint surface have always been a difficult problem in orthopedics, and scholars at home and abroad have made various studies.
[0003] In the prior art, the application number CN114306732A discloses a kind of cartilage repair promoting hydrogel material and its preparation method and application. It uses TGF-β3 to pretreat BMSC to obtain TGF-β3-miRNA-cellular vesicle, and obtains TGF-β3-miRNA-cellular vesicle BMSC by co-culturing BMSC with TGF-β3-miRNA-cellular vesicle, mixes the obtained product with biocompatible hydrogel uniformly to obtain cartilage repair promoting hydrogel material. The material overcomes the limitations of using TGF-β3 to promote BMSC chondrogenic differentiation due to the synergistic effect between TGF-β3-miRNA-cellular vesicles, improves the efficiency of BMSC chondrogenic differentiation, has a remarkable excellent cartilage repair effect, and can be applied to the treatment of damaged cartilage. Although this method can partially restore joint function and relieve pain in patients. However, only fibrocartilage can be formed, and the mechanical properties of the repaired tissue are poor, which can easily break down and degenerate with time and pressure.
[0004] Piezoelectric materials, as a typical mechanoelectric transduction material, can convert various mechanical stimuli into electrical signals based on the piezoelectric effect. They are one of the best options for generating localized electrical stimulation signals that can be driven by changes in internal potential caused by deformation under external force. While the piezoelectric polymer poly(vinylidene fluoride) (PVDF), with its excellent piezoelectric properties and excellent processability, possesses excellent properties as an electroactive biomaterial, it is non-biodegradable, posing a problem for the success of cartilage repair. The biodegradable piezoelectric copolymers poly(l-lactic acid) (PLLA) and poly(lactic acid) (PLA) exhibit relatively weak piezoelectric properties. Therefore, the search for a piezoelectric biomaterial with excellent biodegradability and biocompatibility is urgent. Summary of the Invention
[0005] The purpose of the present invention is to provide a hydrogel, preparation method and application thereof for promoting cartilage repair by utilizing piezoelectric effect in order to solve at least one of the above technical problems.
[0006] The present invention achieves the above-mentioned object through the following technical solutions: a hydrogel that promotes cartilage repair by utilizing the piezoelectric effect, comprising a hydrogel body, wherein the hydrogel is a biodegradable three-dimensional piezoelectric hydrogel comprising potassium sodium niobate (KKN), polyvinyl alcohol (PVA) and polyacrylic acid (PAA), wherein potassium sodium niobate (KKN) is filled in the gaps between the polyvinyl alcohol (PVA) and polyacrylic acid (PAA) gels;
[0007] The preparation method comprises the following steps:
[0008] Step 1: Prepare a 4 wt% PVA solution: Mix 100 mL of deionized water and 4 g of PVA in a beaker, then stir in a 90°C water bath for 30 min until the PVA is completely dissolved to obtain a transparent solution.
[0009] Step 2: Prepare 10 mol / L NaOH solution: weigh 20 g NaOH into a small beaker, then add deionized water and stir until the NaOH is dissolved. Finally, use a 50 ml volumetric flask to make up to volume.
[0010] Step three, preparation of PVA / PAA / KNN composite piezoelectric hydrogel: 5 mL of 4wt% PVA solution and 0.05 g of potassium sodium niobate (KNN) are added into a beaker and stirred, then 0.01 g of N, N'-methylene bisacrylamide (BIS) is added into the beaker and stirred again to obtain a dispersion, then 1 mL of acrylic acid is added and stirred, then 0.725 mL of 10 mol / L NaOH solution is added to make the reaction system have a neutralization degree of 50 mol%, and then 100 μL of tetramethyl ethylenediamine (TEMED) is added as a catalyst and stirred; finally, 0.1 g of potassium persulfate (KPS) is added as an initiator and stirred; the final solution is placed in a 50°C water bath for stirring reaction; when the system is observed to be viscous, the stirring is stopped, and the solid in the beaker is taken out and placed in a sealed bag and frozen in a refrigerator at -18°C for 18 hours, and then the PVA / PAA / KNN composite piezoelectric hydrogel is obtained from the refrigerator.
[0011] As a further scheme of the present application: polyvinyl alcohol (PVA) is a gel state with a porous structure, is a linear polymer, is polymerized from vinyl acetate (VA) under certain conditions, and can be dissolved in water in various proportions.
[0012] As a further scheme of the present application: polyacrylic acid (PAA) is a polyelectrolyte with negative charge, is a water-soluble polyelectrolyte with negative charge, contains carboxyl groups on the polymer main chain, and can interact with various other polymers or molecules.
[0013] As a further scheme of the present application: potassium sodium niobate (KNN) is a piezoelectric material, is a ferroelectric material with rich phase structure, and undergoes a series of structural phase transitions from cubic phase (C) to tetragonal phase (T), from tetragonal phase to orthorhombic phase (O), and from orthorhombic phase to rhombohedral phase (R) as the temperature decreases.
[0014] As a further scheme of the present application: in step three, the stirring time of potassium sodium niobate added into the 4wt% PVA solution and the stirring time of N, N'-methylene bisacrylamide are both 15-20 min.
[0015] As a further scheme of the present application: in step three, the obtained dispersion is ultrasonically treated for 15-20 min to make the KNN uniformly dispersed in the dispersion.
[0016] As a further scheme of the present application: in step three, the stirring time after the addition of acrylic acid is 15-20 min.
[0017] As a further scheme of the present application: in step three, the stirring time after adding NaOH solution, the stirring time of adding the catalyst tetramethyl ethylenediamine (TEMED) and the stirring time of adding the initiator potassium persulfate are all 5-10 min.
[0018] The hydrogel promotes cartilage repair by using piezoelectric effect, can generate electric signals to promote chondrogenic differentiation of stem cells and endogenous angiogenesis in response to radio stimulation, finally perfectly regenerates hyaline cartilage at the cartilage defect, and further accelerates the recovery of motor function, and can be applied to the treatment of osteoarthritis by promoting damaged cartilage regeneration.
[0019] The present application has the following beneficial effects: the phase structure of KNN is regulated by using sodium potassium niobate to realize multiphase coexistence, thereby increasing the polarization direction of the electric dipole inside the material under zero field, making it easier to obtain large entropy under the action of an external electric field, and thus the large electrocaloric effect is expected to be obtained; polyvinyl alcohol can be dissolved in water in various proportions, and has good thermal stability; polyacrylic acid is used as the hydrogel matrix; the piezoelectric hydrogel mainly composed of the non-toxic and harmless sodium potassium niobate nanoparticles with excellent piezoelectric properties and polyvinyl alcohol and polyacrylic acid is developed; a biodegradable three-dimensional piezoelectric scaffold is implanted into the knee cartilage defect; when the knee joint moves, the three-dimensional piezoelectric scaffold generates electric charges due to stress extrusion and joint self-friction; the composite piezoelectric hydrogel can generate electric signals to promote chondrogenic differentiation of stem cells and endogenous angiogenesis in response to radio stimulation, finally perfectly regenerates hyaline cartilage at the cartilage defect, and further accelerates the recovery of motor function. The treatment of osteoarthritis by promoting damaged cartilage regeneration has important significance, and the biodegradable three-dimensional piezoelectric scaffold has a wide application prospect in the field of regenerative medicine. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 It is a physical diagram of the preparation process of the composite piezoelectric hydrogel of the present application;
[0021] Figure 2 It is an XRD pattern of KNN, PVA / PAA and PVA / PAA / KNN hydrogel of the present application;
[0022] Figure 3 It is an XRD pattern of PVA / PAA / KNN hydrogel before and after swelling of the present application;
[0023] Figure 4 It is an FTIR spectrum of KNN, PVA / PAA and PVA / PAA / KNN hydrogel of the present application;
[0024] Figure 5 It is a TG curve of PVA / PAA and PVA / PAA / KNN (1 wt% KNN) hydrogel of the present application;
[0025] Figure 6 DTG curves of PVA / PAA and PVA / PAA / KNN (1 wt% KNN) hydrogels of the present application;
[0026] Figure 7 Micro-morphology images of PVA / PAA and PVA / PAA / KNN hydrogels of the present application;
[0027] Figure 8 Formation mechanism of KNN-PAA / PAM biodegradable three-dimensional piezoelectric hydrogel of the present application;
[0028] Figure 9 Schematic diagram of charge generation of pressure-induced PVA / PAA / KNN piezoelectric hydrogel of the present application. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0030] Embodiment one: as shown in the figure, a hydrogel for promoting cartilage repair by using piezoelectric effect, comprising a hydrogel body, the hydrogel body is a biodegradable three-dimensional piezoelectric hydrogel containing potassium sodium niobate (KKN), polyvinyl alcohol (PVA) and polyacrylic acid (PAA), and the potassium sodium niobate KNN is filled in the voids of the polyvinyl alcohol (PVA) and polyacrylic acid (PAA) gel; Figure 1
[0031] The preparation method comprises the following steps:
[0032] Step one, preparing a 4wt% PVA solution: mix 100mL deionized water and 4g PVA in a beaker, then stir in a 90℃ water bath for 30min until the PVA is completely dissolved to obtain a transparent solution;
[0033] Step two, preparing a 10mol / L NaOH solution: weigh 20g NaOH into a small beaker, then add deionized water and stir until the NaOH is dissolved, and finally use a 50ml volumetric flask to make up the volume;
[0034] Step three, preparation of PVA / PAA / KNN composite piezoelectric hydrogel: 5 mL of 4wt% PVA solution and 0.05 g of potassium sodium niobate (KNN) were added to a beaker and stirred, then 0.01 g of N, N'-methylene bisacrylamide (BIS) was added to the beaker and stirred again to obtain a dispersion, then 1 mL of acrylic acid was added and stirred, then 0.725 mL of 10 mol / L NaOH solution was added to make the reaction system 50 mol% neutralization degree, and then 100 μL of tetramethyl ethylenediamine (TEMED) was added as a catalyst and stirred; finally, 0.1 g of potassium persulfate (KPS) was added as an initiator and stirred; the final solution was placed in a 50°C water bath and stirred to react; when the system was observed to be viscous, the stirring was stopped, and the solid in the beaker was taken out and placed in a sealed bag and frozen in the refrigerator at -18°C for 18 hours, and then the PVA / PAA / KNN composite piezoelectric hydrogel was obtained from the refrigerator.
[0035] In this embodiment, in addition to all the technical features in embodiment one, it further includes:
[0036] Polyvinyl alcohol (PVA) is a gel with a porous structure, which is a linear polymer polymerized from vinyl acetate (VA) under certain conditions, can be dissolved in water in various proportions, is a hard glassy solid at room temperature, and the product has glue solution, latex, white powder, translucent beads and thin slices, etc. It has good thermal stability and can be dissolved in water at any ratio. The aqueous solution is a uniform and transparent liquid.
[0037] Polyacrylic acid (PAA) is a negatively charged polyelectrolyte, which is a negatively charged water-soluble polyelectrolyte containing carboxyl groups in its polymer backbone, can interact with a variety of other polymers or molecules (e.g. hydrogen bonds, ionic bonds, complexation, etc.), is an excellent hydrogel matrix, and has high mechanical strength, ionic conductivity, etc. It is an ideal candidate material for flexible electronic devices, sensors and mobile energy.
[0038] Potassium sodium niobate (KNN) is a piezoelectric material, which is a ferroelectric material with rich phase structure, non-toxic and biodegradable. With the decrease of temperature, it successively undergoes a series of structural phase transitions from cubic phase (C) to tetragonal phase (T), from tetragonal phase to orthorhombic phase (O), and from orthorhombic phase to rhombohedral phase (R). By adjusting the phase structure of KNN to realize the coexistence of multiple phases, the polarization direction of the internal electric dipole under zero field is increased, which makes it easier to obtain large entropy change under the action of external electric field, so as to obtain large electrocaloric effect.
[0039] In this embodiment, in addition to all the technical features in embodiment one, it further includes:
[0040] In step three, the stirring time of the potassium sodium niobate added into the 4wt% PVA solution and the stirring time of the added N,N'-methylene bisacrylamide are both 15-20 min.
[0041] In step three, for the obtained dispersion, the dispersion is ultrasonically treated for 15-20 min, so that the KNN is uniformly dispersed in the dispersion.
[0042] In step three, the stirring time after the addition of the acrylic acid is 15-20 min.
[0043] In step three, the stirring time after the addition of the NaOH solution, the stirring time after the addition of the catalyst tetramethyl ethylenediamine (TEMED) and the stirring time after the addition of the initiator potassium persulfate are all 5-10 min.
[0044] The preparation of the hydrogel is promoted by the piezoelectric effect, the hydrogel can generate an electric signal to promote the chondrogenic differentiation of stem cells and endogenous angiogenesis in response to radio stimulation, and finally perfectly regenerate hyaline cartilage at the cartilage defect site, thereby accelerating the recovery of motor function. The hydrogel can be applied to the treatment of osteoarthritis by promoting the regeneration of damaged cartilage.
[0045] As shown in Figures 2-3 Example four, a preparation method of a hydrogel, including a hydrogel body, the hydrogel body is subjected to X-ray diffraction analysis, PVA / PAA / KNN appears characteristic peaks consistent with KNN near 2θ=22° and 2θ=31.90°, and appears an amorphous peak same as PVA / PAA at 2θ=19.5°, indicating that KNN is wrapped into the gel network result, PVA / PAA / KNN (1wt% KNN) has the same characteristic peaks before and after swelling, indicating that the KNN in the PVA / PAA / KNN (1wt% KNN) composite piezoelectric hydrogel after swelling is still wrapped by the gel network, and has not completely fallen off from the gel structure.
[0046] Example five, as shown in Figure 4As shown in FIG. 6, a method for preparing a cartilage repair hydrogel using a piezoelectric effect, Fourier transform infrared spectroscopy analysis was performed on the hydrogel. In the infrared spectra of KNN and PVA / PAA and PVA / PAA / KNN hydrogels, 653 cm-1 corresponds to the Nb-O bond, which is a characteristic peak of KNN. The characteristic peaks of PAA / PVA include: 3330 cm-1 is the hydrogen bond association absorption peak of the hydroxyl group; 2925 cm-1 corresponds to the absorption peak of the carbon-hydrogen bond (C-H) of the alkyl group; the absorption peak at 1625 cm-1 is due to the anti-symmetrical stretching vibration of the carboxyl anion (-COO-) in the PAA molecule; the absorption peak at 1457 cm-1 is due to the symmetrical stretching vibration of -COO-. Similar characteristic peaks of KNN and PAA / PVA hydrogels can be seen in the infrared spectrum of PVA / PAA / KNN (1 wt% KNN) hydrogel.
[0047] Example Six, as Figures 5-6 shown, a method for preparing a cartilage repair hydrogel using a piezoelectric effect, thermogravimetric analysis was performed on the hydrogel. By comparing the TG curves of PVA / PAA and PVA / PAA / KNN hydrogels, it was found that the initial thermal weight loss temperature of PVA / PAA hydrogel was at 67.7°C, while the initial thermal weight loss temperature of the hydrogel containing KNN was at 64.4°C. At this time, the water molecules in the pores of the two hydrogels evaporate, and this temperature is similar to the evaporation temperature of water molecules in normal environment, which indicates that their heat resistance is poor. At 1000°C, the residual mass of KNN is 98.06%, and the mass loss may be caused by the thermal decomposition of water and impurities attached to the surface of KNN; the residual mass of PVA / PAA hydrogel is 1.68%, and the substance that is not thermally decomposed may be some impurities introduced during the preparation of the gel; the residual mass of PVA / PAA / KNN (1 wt%) piezoelectric hydrogel is 5.60%, and the substance that is not thermally decomposed should be KNN. This indicates that KNN has been successfully compounded in PVA / PAA hydrogel. The maximum decomposition rate temperature of PVA / PAA hydrogel is 377°C, and the maximum decomposition rate temperature of PVA / PAA / KNN (1 wt%) piezoelectric hydrogel is 450°C.
[0048] Example Seven, as Figures 7-9As shown, a preparation method of a cartilage repair hydrogel using a piezoelectric effect is used to analyze the hydrogel by scanning electron microscopy, and the microstructure of PVA / PAA and PVA / PAA / KNN hydrogels is observed. By comparing the morphologies of the two hydrogels, it can be found that the PVA / PAA hydrogel in Figure a and Figure b has a clear three-dimensional network structure. In Figure c and Figure d, it can be observed that the PVA / PAA / KNN hydrogel forms a clear interpenetrating network structure due to the compounding of KNN. Because KNN acts as a crosslinking agent and a filler in the gel system, it crosslinks with hydroxyl, carboxyl, amide and other groups, thereby forming an interpenetrating network structure.
[0049] Working principle: polyvinyl alcohol / polyacrylic acid / KNN (PVA / PAA / KNN) piezoelectric hydrogel is prepared by combining free radical polymerization and freeze-thaw method. First, 4 wt% polyvinyl alcohol (PVA) solution and potassium sodium niobate (KNN) are added to a beaker and stirred uniformly to obtain a PVA / KNN dispersion; then N,N'-methylenebisacrylamide (BIS) is added to the beaker and stirred uniformly, followed by ultrasonic treatment of the dispersion to disperse KNN uniformly. Then acrylic acid (AA) and NaOH solution are added, and after stirring uniformly, a milky white PVA / AA / KNN dispersion is obtained; then the catalyst tetramethyl ethylenediamine (TEMED) and the initiator potassium persulfate (KPS) are added in turn, and after stirring uniformly, the system is placed in a 50°C water bath for stirring reaction. When the system is observed to be viscous, stop stirring, take out the solid in the beaker and put it into a sealed bag, and then put it into a refrigerator at-18°C for 18h. Then take it out of the refrigerator to obtain PVA / PAA / KNN composite piezoelectric hydrogel.
[0050] It is obvious to a person skilled in the art that the present application is not limited to the details of the above exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or essential characteristics of the present application. Therefore, the embodiments should be regarded as exemplary and non-limiting, and the scope of the present application is defined by the appended claims rather than the above description, and therefore all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be included in the present application. Any reference signs in the claims should not be regarded as limiting the claims involved.
[0051] In addition, it should be understood that although the present specification is described in terms of embodiments, not every embodiment contains only one independent technical solution, and the description of the specification is only for the sake of clarity, and those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can be appropriately combined to form other embodiments that those skilled in the art can understand.
Claims
1. A hydrogel for promoting cartilage repair using the piezoelectric effect, comprising a hydrogel body, characterized in that: The hydrogel body is a biodegradable three-dimensional piezoelectric hydrogel comprising sodium potassium niobate, polyvinyl alcohol and polyacrylic acid, and the sodium potassium niobate KNN is filled in the gaps of the polyvinyl alcohol and polyacrylic acid gels; The preparation method of the hydrogel comprises: Step 1: Prepare a 4 wt% PVA solution: Mix 100 mL of deionized water and 4 g of PVA in a beaker, then stir in a 90°C water bath for 30 min until the PVA is completely dissolved to obtain a transparent solution. Step 2: Prepare 10 mol / L NaOH solution: weigh 20 g NaOH into a small beaker, then add deionized water and stir until the NaOH is dissolved. Finally, use a 50 ml volumetric flask to make up to volume. Step 3: Preparation of PVA / PAA / KNN composite piezoelectric hydrogel: 1) Add 5 mL of 4 wt% PVA solution and 0.05 g of sodium potassium niobate to a beaker and stir. 2) Add 0.01 g of N,N'-methylenebisacrylamide to the beaker and stir again to obtain a dispersion; 3) Add 1 mL of acrylic acid and stir, then add 0.725 mL of 10 mol / L NaOH solution to make the reaction system 50 mol% neutralized; 4) Continue stirring and add 100 μL of tetramethylethylenediamine as a catalyst and continue stirring; 5) Add 0.1g potassium persulfate as an initiator and stir. Place the final solution in a 50°C water bath and stir to react. 6) When the system becomes viscous, stop stirring, remove the solid from the beaker, place it in a sealed bag, and freeze it in a refrigerator at -18°C for 18 hours. Then take it out of the refrigerator to obtain the PVA / PAA / KNN composite piezoelectric hydrogel.
2. The hydrogel according to claim 1, wherein: The polyvinyl alcohol is in a gel state with a porous structure and is a linear high molecular polymer. It is polymerized from vinyl acetate under certain conditions and can be dissolved in water in various proportions.
3. The hydrogel according to claim 1, wherein: The polyacrylic acid is a negatively charged polyelectrolyte, which is a negatively charged water-soluble polyelectrolyte. The main chain of the polymer contains carboxyl groups, and it can interact with a variety of other polymers or molecules intermolecularly.
4. The hydrogel according to claim 1, wherein: The sodium potassium niobate is a piezoelectric material and a ferroelectric material with a rich phase structure. As the temperature decreases, it undergoes a series of structural phase transitions from cubic phase to tetragonal phase, from tetragonal phase to orthorhombic phase, and from orthorhombic phase to rhombohedral phase.
5. The hydrogel according to claim 1, wherein: In step 3, the stirring time when potassium sodium niobate is added to the 4 wt % PVA solution and the stirring time when N,N'-methylenebisacrylamide is added are both 15-20 minutes.
6. The hydrogel according to claim 1, wherein: In the step 3, the obtained dispersion is ultrasonicated for 15-20 minutes to ensure that the KNN is evenly dispersed in the dispersion.
7. The hydrogel according to claim 1, wherein: In the step 3, the stirring time after adding acrylic acid is 15-20 minutes.
8. The hydrogel according to claim 1, wherein: In the step 3, the stirring time after adding the NaOH solution, the stirring time after adding the catalyst tetramethylethylenediamine, and the stirring time after adding the initiator potassium persulfate are all 5-10 minutes.
9. A hydrogel for promoting the regeneration of damaged cartilage to treat osteoarthritis, characterized by: The hydrogel is prepared by the preparation method of claim 1. The hydrogel generates electrical signals in response to radio stimulation to promote the differentiation of stem cells into cartilage and endogenous angiogenesis, ultimately perfectly regenerating hyaline cartilage at the cartilage defect, thereby accelerating the recovery of motor function.
Citation Information
Patent Citations
Hydrogel material for promoting cartilage repair as well as preparation method and application of hydrogel material
CN114306732A
Preparation method and application of double-network polyvinyl alcohol-polyacrylic acid hydrogel
CN113174062A
Piezoelectric hydrogel for diabetes wound repair as well as preparation method and application of piezoelectric hydrogel
CN116531553A